2013
DOI: 10.4321/s0004-05922013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Características de silagens de milho inoculadas com Lactobacillus Buchneri e L. plantarum

Abstract: RESUMOObjetivou-se avaliar o padrão fermentativo, estabilidade aeróbia e valor alimentício de silagens de milho inoculadas com Lactobacillus buchneri associado ou não ao L. plantarum. Os tratamentos avaliados foram: silagem de milho sem inoculação (controle); silagem de milho inoculada com L. buchneri NCIMB 40788 (1x10 5 UFC/g forragem); silagem de milho inoculada com L. buchneri NCIMB 40788 e L. plantarum MA18/5U (1x10 5 UFC/g forragem). A inoculação com L. buchneri promoveu alterações no padrão fermentativo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…However, inoculation of corn silage with L. buchneri did not enhance the performance of bulls fed the 60:40 F:C ratio likely because of the reduction in NDF and DM digestibility. The lack of positive results on animal performance regarding inoculation of silages with L. buchneri has been reported earlier (Salvo et al 2013;Addah et al 2014). Furthermore, feed efficiency was not affected by treatments because a greater DMI intake observed in bulls fed the 40:60 F:C_I diet led an increase in ADG, while the reduction in DMI observed with other treatments was associated with a reduction in ADG.…”
Section: Discussionmentioning
confidence: 62%
“…However, inoculation of corn silage with L. buchneri did not enhance the performance of bulls fed the 60:40 F:C ratio likely because of the reduction in NDF and DM digestibility. The lack of positive results on animal performance regarding inoculation of silages with L. buchneri has been reported earlier (Salvo et al 2013;Addah et al 2014). Furthermore, feed efficiency was not affected by treatments because a greater DMI intake observed in bulls fed the 40:60 F:C_I diet led an increase in ADG, while the reduction in DMI observed with other treatments was associated with a reduction in ADG.…”
Section: Discussionmentioning
confidence: 62%
“…As reported by Danner et al [13] and Muck [46], when using heterofermentative lactic acid bacteria, such as L. buchneri, aerobic stability was improved in all treated silages due to the low number of yeasts in these silages. Numerous studies have proved that inoculation with L. buchneri inhibited the growth of molds and yeast and, consequently, improved the aerobic stability of silage [8,17,18,[47][48][49][50][51][52][53]. The improved aerobic stability is mainly due to the formation of acetic acid and 1,2-propanediol during degradation of lactic acid by L. buchneri under anaerobic conditions [45,47].…”
Section: Discussionmentioning
confidence: 99%
“…As a heterofermentative lactic acid bacterium, L. buchneri not only plays an important role in improving the aerobic stability of ensiled forage but also can enhance the quality and nutritional value of silage [10][11][12]. A considerable number of investigations have been conducted on the effects of L. buchneri on whole-plant corn or alfalfa silage quality, and the results confirmed that L. buchneri could effectively enhance the aerobic stability of silage by inhibiting spoilage microbes such as yeasts and molds, thereby prolonging the contact of silage with air [13][14][15][16][17][18]. Additionally, the inoculation of L. buchneri could lower the amino-peptidic nitrogen and butyric acid in ensiled forages [14,19].…”
Section: Introductionmentioning
confidence: 90%
“…A silagem de sorgo (Tabela 3) teve seus valores de MS influenciada pelos tratamentos (P = 0,0081), não sendo observados efeitos para as idades de corte (P > 0,05) com os teores de MS variando de 27,5 a 29,1% na primeira idade de corte a 29,2 a 29,7% na segunda idade de corte. Salvo et al (2013) avaliando a composição nutricional de silagens de milho com cepas homo e heterofermentativas, avaliaram que as silagens com bactérias heterofermentativas quando comparada a silagem controle apresentaram redução no teor de MS, mostrando que ocorreram perdas sob forma de gases e efluentes no processo de fermentação heterolática que ocorreu pelo controle de microrganismos indesejáveis durante o processo fermentativo. Tabela 3.…”
Section: Resultsunclassified